2009
DOI: 10.2754/avb200978010057
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Metabolism of Dairy Cows Fed Bean Seeds (Vicia faba) with Different Levels of Anti-Nutritional Substances

Abstract: The aim of this study was to determine the effect of selected bean cultivars with different levels of anti-nutritional substances on performance and metabolism of dairy cows. In the current twelve-week-long study, 32 dairy cows at 3 to 6 weeks after parturition were divided into four groups. Diets were balanced to have an analogical content of crude protein and energy. Experimental groups (MI, ME, MET) were mixed to the milking concentrate consisting of 20% bean seeds (MI -MISTRAL cultivar with a low content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Data on the effects of feeding fava bean as a replacement especially for rapeseed meal in grass silage-based dairy cow diets is rather limited, to our knowledge. Substitution of either soybean or rapeseed meal with fava bean in supplemented cereal grain-based concentrate at a rate of 10 to 35% had no adverse effects on DMI, milk yields, or milk protein yields in early studies conducted on corn silage or brome hay diets (Ingalls and McKirdy, 1974;Ingalls et al, 1980), or in more recent studies conducted on corn silage-based TMR or oat hay diets (Melicharová et al, 2009;Tufarelli et al, 2012). In contrast, Mordenti et al (2007) substituted soybean with a mixture of fava bean and pea in an alfalfa hay-based TMR diet and found a decrease in silage intake and milk yield.…”
Section: Introductionmentioning
confidence: 89%
“…Data on the effects of feeding fava bean as a replacement especially for rapeseed meal in grass silage-based dairy cow diets is rather limited, to our knowledge. Substitution of either soybean or rapeseed meal with fava bean in supplemented cereal grain-based concentrate at a rate of 10 to 35% had no adverse effects on DMI, milk yields, or milk protein yields in early studies conducted on corn silage or brome hay diets (Ingalls and McKirdy, 1974;Ingalls et al, 1980), or in more recent studies conducted on corn silage-based TMR or oat hay diets (Melicharová et al, 2009;Tufarelli et al, 2012). In contrast, Mordenti et al (2007) substituted soybean with a mixture of fava bean and pea in an alfalfa hay-based TMR diet and found a decrease in silage intake and milk yield.…”
Section: Introductionmentioning
confidence: 89%
“…Brunschwig and Lamy () showed that the use of 30% of ground fava bean in the feed of dairy cows does not alter feed consumption, milk production (higher than 30 kg per cow per day), or milk composition (crude protein or lipid). Recently, it was concluded that the various cultivars of fava bean could differently affect performance and metabolism of dairy cattle, although even fava bean cultivars with a high content of antinutritional factors can be used up to 20% in the feed without any alteration of cow metabolism and performance (daily milk yield and protein and lactose production; Melicharová and others ). Noteworthy is that when young Mediterranean bulls were fed with fava bean concentrate‐enriched feed they produced meat with a more favorable lipid profile than when fed with soy concentrate‐enriched feed, as the meat was lower in fat percentage, cholesterol, and total saturated fatty acid content (Calabrò and others ).…”
Section: Numerous and Valuable Uses Of Fava Bean As Feedmentioning
confidence: 99%